Maternal mortality in the Cayetano Heredia National Hospital (1985-1992) - Maradiegue Méndez, Eduardo (2015)
Retrospective, transversal, clinical, epidemiological, case-control 75 maternal deaths in the Cayetano Heredia National Hospital (HNCH) between 1985 and 1992. The control group consisted of 193 patients systematically selected population of pregnant and postpartum study They did not die. The hospital maternal mortality rate was 210.3 per 100,000 live births, the highest was obtained for 1992 with 335.9. The most frequent causes of death were direct with 86.6%, the main infection, hypertension and bleeding. Risk factors for infection were: 5 or more pregnancies (OR = 1.5), septic shock (OR = 7.0), anemia (OR = 4.5), and acute renal failure (OR = 14.5); for hypertension: age over 34 years (OR = 3.5) and under 21 years (OR = 1, 1), average higher than 126 mm Hg (OR = 6.1) blood pressure, severe edema (OR = 4 , 0) and HELLP (OR = 47.0) syndrome; and, for bleeding, age over 34 years (OR = 1.5). 50% of patients died within the first 24 hours of hospitalization while 70% of controls remained more than 72 hours. Cerebro-vascular septic shock, hypovolemic shock accident and were the main causes of death for infection, hypertension and bleeding respectively.